Pain in rheumatic diseases – ethiology and management - Borysewicz, Krzysztof; Szechiński, Jacek (Przewodnik Lekarza/Guide for GPs, 2006)
Arthritis and other non-inflammatory musculoskeletal disorders are very common in the adult human population. One of the most common problem in these diseases is pain. In this paper characterization of pain types in rheumatic diseases, etiology and analgetic management was described. Health care providers should use the best current evidence in making decisions about the treatment of individual patients. Pharmacotherapy, patients education, weight control, rehabilitation programmes, cognitive behavioral strategies and surgery are used in many of these conditions.